Charge coupled device based on optical tomography system in detecting air bubbles in crystal clear water - Juliza Jamaludin; Rahim R.A.; Rahim H.A.; Fazalul Rahiman M.H.; Mohd Muji S.Z.; Rohani J.M. (Elsevier Ltd, 2024)
Indexed by WOS/ Scopus